Defining biological thresholds associated to plant water status for monitoring water restriction effects: Stomatal conductance and photosynthesis recovery as key indicators in potato - Ramírez, D.; Yactayo, W.; Rens, L.R.; Rolando, J.L.; Palacios, S.; Mendiburu, F. de; Mares, V.; Barreda, C.; Loayza, H.; Monneveux, P.; Zotarelli, L.; Khan, A.; et al. (Elsevier, 2016)
The definition of irrigation schedules depends on the understanding of the response of key plant traits to different water restriction characteristics with the aim to avoid physiological impairment. In this study, different timings (at tuber initiation and bulking) and intensities (four soil moisture levels) of water restriction were tested in the potato crop. The temporal patterns of mid-morning or maximum, light saturated stomatal conductance (gs_max), recovery of net photosynthesis (Arecovery), stem water potential ( stem), carbon isotope discrimination in tubers ( tuber), plant water concentration (PWC), photochemical reflectance index (PRI) and crop water stress index (CWSI) were analyzed. Early-severe water restriction caused a drastic yield reduction, with low recovery of physiological responses (gs_max, tuber, stem, CWSI, Arecovery) after 15 days of post-restriction irrigation and even a continued reduction of some of them (PWC, PRI). It also caused a prolonged gs_max reduction below 0.05 mol H2O m-2 s-1 (˜ 5 µmol CO2 m-2 s-1 of net photosynthesis) suggesting that this value defines a physiological severity threshold in potato, under which a metabolic impairment occurs. CWSI and PRI showed a close linear (R2 = 0.76) and no linear (natural logarithm function, R2 = 0.67) relationship with gs_max respectively. In cloudless dry environments, irrigation schedules in potato should aim to avoiding CWSI values higher than 0.4, especially until before of maximum canopy cover establishment. A close relationship between Arecovery at maximum stress moment and yield reduction was found. The strong relationship between the measured traits (except PWC and stem) and final yield at maximum stress moment found in the present study warrants further research on drought phenotyping immediately before post-restriction irrigation or when the defined severity threshold in potato is reached.